METHODISM IN WILLIAM BLAKE'S THE CHIMNEY SWEEPER - Susie Chrismalia Garnida; Mateus Rudi Supsiadji (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2018)
This article explores one of Blake's poems entitled The Chimney Sweeper which sees gloomily the condition of child labour during the industrial revolution in Britain. In the poem, it seems that Blake critizes the use of children to work for family income. Especially, this article discusses Blake’s ironical discussion on the Methodism's teaching to work hard in order to have the eternal life in the poem.